The Assisted Nordic Hamstring Curl. Issue 1 (February 2015) - Matthews, Martyn J.; Jones, Paul; Cohen, Daniel; Matthews, Helen
Abstract : ABSTRACT: ASSISTED NORDIC HAMSTRING CURLS PROVIDE A MECHANISM FOR ASSISTING THE LOWER PHASES OF A NORDIC HAMSTRING CURL, ALLOWING TRAINING AT INCREASED HAMSTRING MUSCLE LENGTH POSITIONS AND THE PERFORMANCE OF MORE REPETITIONS. THIS EXERCISE MAY BE USEFUL TO TARGET THE SPECIFIC MUSCLE LENGTHS OR FATIGUE CONDITIONS AT WHICH INJURIES OCCUR.